Impact of COVID-19 on UK stress echocardiography practice: insights from the EVAREST sites. Issue 1 (March 2021) - Dockerill, Cameron; Woodward, William; McCourt, Annabelle; Monteiro, Cristiana; Benedetto, Elena; Paton, Maria; Oxborough, David; Robinson, Shaun; Pearce, Keith; Monaghan, Mark J; Augustine, Daniel X; Leeson, Paul
Abstract : Introduction: Healthcare delivery is being transformed by COVID-19 to reduce transmission risk but continued delivery of routine clinical tests is essential. Stress echocardiography is one of the most widely used cardiac tests in the NHS. We assessed the impact of the first (W1 ) and second (W2 ) waves of the pandemic on the ability to deliver stress echocardiography. Methods: Clinical echocardiography teams in 31 NHS hospitals participating in the EVAREST study were asked to complete a survey on the structure and delivery of stress echocardiography as well as its impact on patients and staff in July and November 2020. Results were compared to stress echocardiography activity in the same centre during January 2020. Results: 24 completed the survey in July, and 19 NHS hospitals completed the survey in November. A 55% reduction in the number of studies performed was reported in W1, recovering to exceed pre-COVID rates in W2 . The major change was in the mode of stress delivery. 70% of sites stopped their exercise stress service in W1, compared to 19% in W2 . In those still using exercise during W1, 50% were wearing FFP3/N95 masks, falling to 38% in W2 . There was also significant variability in patient screening practices with 7 different pre-screening questionnaires used in W1 and 6 in W2 . Conclusion: Stress echocardiography delivery restarted effectively after COVID-19 with adaptations to reduce transmission that means activity has been able to continue, and exceed, pre-COVID-19 levels during the second wave. Further standardization of protocols for patient screening and PPE may help further improve consistency of practice within the United Kingdom.